Jewish Cultural Encounters in the Ancient Mediterranean and near Eastern World - Popović, Mladen 1977-; Schoonover, Myles; Vandenberghe, Marijn (Leiden BRILL, 2017)
Contents -- Chapter 1 Ancient Jewish Cultural Encounters and a Case Study on Ezekiel -- Chapter 2 Taming Egypt: The Impact of Persian Imperial Ideology and Politics on the Biblical Exodus Account -- Chapter 3 Exchange, Replacement, or Acceptance? Two Examples of Lending Deities among Ethnic Groups in Elephantine -- Chapter 4 Netting Marduk? The Concept of Hidden Transcripts and the Transfer of Cultural Knowledge from Mesopotamian to Judean Texts -- Chapter 5 The Prayer of Nabonidus in the Light of Hellenistic Babylonian Literature -- Chapter 6 Levels of Meaning and Textual Polysemy in Akkadian and Hebrew Exegetical Texts -- Chapter 7 "Judaism" and "Hellenism": Martin Hengel's Work in Perspective -- Chapter 8 Choosing Between Papyrus and Skin: Cultural Complexity and Multiple Identities in the Qumran Library -- Chapter 9 What Does India Have to Do with Jerusalem? Ben Sira, Language, and Colonialism -- Chapter 10 Hybridity, Hydrology, and Hidden Transcript: Sirach 24 and the Judean Encounter with Ptolemaic Isis Worship -- Chapter 11 Reflections on the Cultural Encounter between the Jews and the Greeks and Romans in Jewish Coin Iconography of the Hellenistic-Roman Period -- Chapter 12 Philo's Greek Scriptures and Cultural Symbiosis -- Chapter 13 "I Wish Those Who Unsettle You Would Mutilate Themselves!" (Gal 5:12): Circumcision and Emasculation in the Letter to the Galatians -- Chapter 14 Rabbis and Romanization: A Review Essay -- Chapter 15 Subversion and Subculture: Jewish Time-Keeping in the Roman Empire -- Chapter 16 Elijah's Cave in Haifa: Whose Holy Site is this Anyway? -- Index of Modern Authors -- Index of Ancient Sources
Keywords: Jews--Mediterranean Region--History--Congresses; Bible ; Old Testament ; Criticism, interpretation, etc ; Congresses; Dead Sea scrolls ; Congresses; Jews ; Mediterranean Region ; History ; Congresses; Jews ; Middle East ; History ; Congresses; Judaism ; Mediterranean Region ; History ; Congresses; Judaism ; Middle East ; History ; Congresses; Electronic books